Analisis Keanekaragaman Tumbuhan Invasif Di Kawasan Hutan Pantai Balekambang Desa Srigonco Kecamatan Bantur Kabupaten Malang - Miftahul Mukarromah; Ari Hayati; Hasan Zayadi (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2020)
Balekambang Beach is the most visited beach destination in Malang Regency until the end of 2015. One of the invasive pathways of invasive plants is Tourism. The purpose of this study was to identify invasive plant species, diversity and compare the value of the diversity index with abiotic factors.This research method is descriptive with systematic sampling techniques using Belt Transect, and measurements of abiotic factors include edafic factors and climatic micro factors. Invasive alien plant species found in the Balekambang coastal forest are identified as seventeen species namely (Hemighraphis glaucescens), (Oplismenus sp), (Amomum coccineum), (Arenga obtusifolia), (Leucaena leucochephana), (Mimosa sp), (Cassia siamea), (Eupatorium odoratum), (Hyptis capitata), (Cynodon dactylon), (Sida rhombifolia), (Synedrella nudiflora), (Chromolaena odorata), (Leucaena leucochepala), (Mimosa pudica), and (Ruellia tuberosa) with the index value of invasive plant diversity in protected forests and production classified as high compared to mangroves. The results of the diversity index value with abiotic factors showed a positive (+) direction on soil sailinity where the R2 value was 0.5606 or 50%, which means it showed a relationship between soil salinity and an abundance of invasive plants in Balekambang coastal forest area of 50%. Keywords:invasive plants, Balekambang beach, belt transect, diversity ABSTRAK Pantai Balekambang adalah destinasi wisata alam pantai di Kabupaten Malang yang paling banyak dikunjungi hingga akhir tahun 2015.Salah satu jalur invasi dari tumbuhan invasif adalah Tourism (Wisata). Tujuan dari penelitian ini adalah mengidentifikasi jenis tumbuhan invasif, keanekaragaman dan membandingkan nilai indeks keanekaragaman dengan faktor abiotik. Metode penelitian ini deskriptif dengan tehnik pengambilan sampling secara sistematis menggunakan Belt Transect, dan pengukuran faktor abiotik meliputi faktor edafik dan faktor mikro klimatik. Jenis spesies tumbuhan asing invasif yang terdapat di hutan pantai Balekambang diidentifikasi sebanyak tujuh belas spesies yaitu Hemighraphis glaucescens, Oplismenus sp, Amomum coccineum, Arenga obtusifolia, Leucaena leucochephana, Mimosa sp, Cassia siamea, Eupatorium odoratum, Hyptis capitata, Cynodon dactylon, Sida rhombifolia, Synedrella nudiflora.Chromolaena odorata, Leucaena leucochepala, Mimosa pudica, dan Ruellia tuberose dengan nilai indeks keanekaragaman tumbuhan invasif pada hutan lindung dan produksi tergolong tinggi dibanding mangrove. Hasil analisis uji korelasi nilai indeks keanekaragaman dengan faktor abiotik menunjukkan arah positif (+) pada salinitas tanah dimana nilai R2 sebesar 0.5606 atau 50%, yang artinya menunjukkan hubungan antara salinitas tanah dengan kelimpahan tumbuhan invasif di kawasan hutan pantai Balekambang sebesar 50%. Kata kunci: tumbuhan invasif, pantai Balekambang, belt transect, keanekaragaman